PENERAPAN LOCATION-BASED SERVICE PADA LAYANAN INFORMASI BUDAYA INDONESIA DI PERANGKAT MOBILE - AHMAD FAUZI (LPPM, 2015)
Cultural diversity-owned nation Indonesia is a form of wealth that belongs to the nation. However, due to advances in technology and low public awareness about it, slowly disappearing as the nation's culture by outside cultural influences. This study presents the solution to increase public awareness of the nation's culture through a system of location-based service application with a mobile device, where the person with this application will be able to know the local culture based on the location of its existence and also give you information about some places that may not have been registered in the system. Locating by utilizing GPS facilities contained on android mobile devices. This is done so that the community can continue to preserve the history and culture of Indonesia. Keyword: Location-BasedService, Information, Cultural, Mobile